Self Directed Learning Scale at University Context - Masrul, Masrul; Yuliani, Sri (UIBU, 2024)
This research was carried out to investigate a relationship between self-directedness, self-involvement, expressive language, self-assessment, language varieties, metacognitive skills, editing and problem solving, text processing, knowledge rehearsal, idea planning, goal oriented monitoring and evaluating, peer learning, feedback handling, interest enhancement, motivational self-talk, and emotional control and the main and forming factors of self-directedness, self-involvement, expressive language, self-assessment, language varieties, metacognitive skills, editing and problem solving, text processing, knowledge rehearsal, idea planning, goal oriented monitoring and evaluating, peer learning, feedback handling, interest enhancing, motivational self-talk, and emotional control of self directed learning. A convenience sample approach was used to recruit English majors from a range of State University of Yogyakarta. All participants were recruited intentionally, and that they were informed that they might leave the study at any moment either during collecting data. The participant criteria include second-year English major students from various State Universities of Yogyakarta. As the result of pearson correlation in this research, it was found that there was a substantial relationship between the variables examined in this research. Moreover, as the result of factor analysis in this research was found that from the 11 variables included in the research namely self involvement, expressive language, self assessment, language varieties, metacognitive skills, editing and problem solving, Cognition, Metacognition, Social Behavior, and Motivational Regulation, they can be grouped into two main factors. The implications of these findings lie in a deeper understanding of the underlying conceptual structure of self-directed learning in a university context. With the identification of the key factors emerging from these variables, a more focused approach can be developed to enhance students' self-directed learning. This can also aid in the development of more precise and measurable assessment instruments to gauge progress in crucial aspects of self-directed learning. Thus, the implications of these findings can enrich teaching and learning practices in higher education settings.